2015
DOI: 10.1021/acs.jctc.5b00037
|View full text |Cite
|
Sign up to set email alerts
|

EQeq+C: An Empirical Bond-Order-Corrected Extended Charge Equilibration Method

Abstract: The extended charge equilibration (EQeq) scheme computes atomic partial charges using the experimentally measured ionization potentials and electron affinities of atoms. However, EQeq erroneously predicts constant (environment independent) charges for high-oxidation-state transition metals in amine-templated metal oxide (ATMO) compounds, contrary to the variation observed in iterative Hirshfeld (Hirshfeld-I) charges, bond-valence sum calculations, and formal oxidation state calculations. To fix this problem, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…Afterward, Martin-Noble et al found that the EQeq method failed to predict the partial charges of TMs with high oxidation states in the amine-templated metal oxide (ATMO) complexes. 880 They then added a correction term into the EQeq scheme on the basis of the relationship between the bond order and bond distance proposed by Pauling (see eq 123 , where n means the bond order, r means the bond distance, with r 0 and b as two parameters; this relationship was also used in the bond valence sum (BVS) model 881 and CM5 charge correction 723 ). The new method was termed as the EQeq+C method.…”
Section: Classical Modeling Of Metal Ions: the Polarizable Modelmentioning
confidence: 99%
“…Afterward, Martin-Noble et al found that the EQeq method failed to predict the partial charges of TMs with high oxidation states in the amine-templated metal oxide (ATMO) complexes. 880 They then added a correction term into the EQeq scheme on the basis of the relationship between the bond order and bond distance proposed by Pauling (see eq 123 , where n means the bond order, r means the bond distance, with r 0 and b as two parameters; this relationship was also used in the bond valence sum (BVS) model 881 and CM5 charge correction 723 ). The new method was termed as the EQeq+C method.…”
Section: Classical Modeling Of Metal Ions: the Polarizable Modelmentioning
confidence: 99%
“…Whereas the determination of atomic charge by theoretical methods is not unified, attempts to find a robust method for its determination have been made from time-to-time. For instance, Stasyuk and coworkers [104], as well as several others [195], have recently proposed new models for evaluating charges that could be utilized for arriving at a fundamental understanding of some chemical systems, including endohedral fullerenes. Evidently, atomic charge is certainly a valuable property [196] that will continue to play a crucial role in the understanding systems in diverse areas of science.…”
Section: Is the Concept Of Atomic Charge Meaningful?mentioning
confidence: 99%
“…The electrostatic potential inside the MOF is typically modelled by assigning a point charge to each MOF atom; point charges are assigned on the molecular model for the adsorbate as well (as is the case for CO 2 [31]), thereby completing the description of the electrostatic interaction of the adsorbate with the MOF. Quick/cheap charge equilibration [Qeq [175]] methods and its variants [EEM[176], , PQeq[177], SQE[178], SCQeq[179], EQeq[180], MEPO-Qeq[181], FCQeq[182], I-Qeq[182], , EQeq+C[183], and SQE-MEPO[184]] are commonly used to assign point charges to atoms of a MOF. However, point charges derived from the electronic density obtained from a first principles calculation on the particular MOF are generally considered more reliable [32].…”
Section: Computation-ready Crystal Structuresmentioning
confidence: 99%